(Al3+, Nb5+) co–doped CaCu3Ti4O12: An extended approach for acceptor–donor heteroatomic substitutions to achieve high–performance giant–dielectric permittivity. Issue 1 (January 2018) - Boonlakhorn, Jakkree; Kidkhunthod, Pinit; Chanlek, Narong; Thongbai, Prasit
Abstract: Substitution of (Al 3+, Nb 5+ ) co–dopants into TiO6 octahedral sites of CaCu3 Ti4 O12 ceramics, which were prepared by a solid state reaction method and sintered at 1090 °C for 18 h, can cause a great reduction in a low–frequency loss tangent (tanδ≈0.045–0.058) compared to those of Al 3+ or Nb 5+ single–doped CaCu3 Ti4 O12 . Notably, very high dielectric permittivities of 2.9 − 4.1 × 10 4 with good dielectric–temperature stability are achieved. The room–temperature grain boundary resistance (Rgb ≈0.37–1.17 × 10 9  Ω.cm) and related conduction activation energy (Egb ≈0.781–0.817 eV), as well as the non–Ohmic properties of the co–doped ceramics are greatly enhanced compared to single–doped ceramics (Rgb ≈10 4 –10 6  Ω cm and Egb ≈0.353–0.619 eV). The results show the importance of grain boundary properties for controlling the nonlinear–electrical and giant–dielectric properties of CaCu3 Ti4 O12 ceramics, supporting the internal barrier layer capacitor model of Schottky barriers at grain boundaries.